Analisis Perbandingan Saham ADRO Dan ADMR Pasca Covid 19 - Prianti, Dela; Anggi, Miftha Maulida; Sahfitri, Nurmaya Dewi; Sari, Reny Tri Viola; Harahap, Muhammad Ikhsan (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
In the investment world, stock prices are very important to know the advantages and disadvantages when investors want to buy shares. The purpose of this study was to analyze the difference in post-Covid 19 Admr and Adro stock prices whether they have increased or decreased. In this study using a type of qualitative research with a descriptive approach. The research data is sourced from secondary data takeen from scientific journals/thesis, books. Data collection techniques were taken from the tradingview website by looking at Adro and Admr stock prices. The results of the discussion this time are that Adro shares have fluctuated from 1550 per share, there has been a decrease of around 4%, namely to 1140 per share in 2020. When Covid was over, the share price per share had increased to 2880 and then decreased by around 8.4%. Meanwhile, Admr shares experienced a decline of 8.55% to 780 per share.